Diseño y construcción de un dispositivo electrónico para el diagnóstico de sensores hall, TPS, relevadores y válvula IAC presentes en las motocicletas de inyección electrónica (2024)
This document contains the development process of an electronic device that can be used to determine the status of certain sensors and actuators present in low and medium displacement motorcycles with electronic injection systems, present in the Colombian vehicle fleet. which was designed based on the operation and failures of the TPS sensors, hall effect sensors, IAC Valves and relays. This in order to be able t